Hubungan antara Critical Thinking Disposition dengan Information Literacy di Media Sosial pada Mahasiswa - Aziza, Dhimas Fachri (Faculty of Psychology, University of Muhammadiyah Malang, Indonesia, 2019)
ABSTRACTThe development of technology and information in this era has made information and science inevitably overflow through social media. This situation is supported by the development of technology such as the existence of computers and internet networks in private, thus makes everyone can easily access information in anywhere and anytime. Nonetheless, information is considered a need for those who relies it in daily life, especially college students. Therefore, it is important to develop ability to find and sort information or scientific reference sources and critical thinking disposition ability to see whether the information is what we really want. The purpose of this study is to examine the relationship between critical thinking disposition and information literacy among students on social media. The sampling technique uses random sampling techniques. The research subjects were 18-24 year old students totaling 269 student. The data was collected using critical thinking disposition scale consisting of 3 aspects which were stated by Ricketts and Rudd namely engagement, cognitive maturity, and innovativeness with 23 items and information literacy scale with 13 items. Test analysis using correlation test and the results show there is a significant relationship of critical thinking disposition and information literacy among students on social media with results (0.00 <0.05).Critical thinking disposition, information literacy.